A new species of Rhinoleucophenga (Diptera: Drosophilidae), parasite of the scale insect pest Praelongorthezia praelonga (Sternorrhyncha: Ortheziidae) from the Brazilian Amazon - Da Silva Carvalho-Filho, Fernando; Duarte, Lucas Baptista; Gottschalk, Marco Silva (Zootaxa, 2019)
A new species of Rhinoleucophenga Hendel from the Brazilian Amazon, R. hesperides sp. nov., was described based on morphology of male and female specimens. The larvae are predators of the eggs and adult females of ensign scales Praelongorthezia praelonga (Douglas) (Hemiptera: Sternorrhyncha: Ortheziidae). Female P. praelonga also serve as a source of honeydew for adult R. hesperides sp. nov. In addition, the puparium of this species was described.